Cost-effectiveness of a self-management and comprehensive training intervention in patients with type 2 diabetes up to 5 years of diagnosis in a specialized hospital in Mexico City - Enrique O Graue-Hernandez; Sergio Hernandez-Jimenez; David Kershenobich-Stalnikowitz; Ana Cristina García-Ulloa; Carlos Alberto Aguilar-Salinas; Denise Arcila-Martínez; Rodrigo Arizmendi-Rodríguez; Humberto Del Valle-Ramírez; Fernanda Garnica-Carrillo; Eduardo González-Flores; Mariana Granados-Arcos; Héctor Infanzón-Talango; et al. (BMJ Open Diabetes Research & Care)
Introduction To assess the cost-effectiveness of a multidisciplinary and comprehensive innovative diabetes care program (CAIPaDi) versus usual treatment in public health institutions.Research design and methods Using a cost-effectiveness analysis, we compared the CAIPaDi program versus usual treatment given in Mexican public health institutions. The analysis was based on the IQVIA Core Diabetes Model, a validated simulation model used to estimate long-term clinical outcomes. Data were prospectively obtained from the CAIPaDi program and from public databases and published papers. Health outcomes were expressed in terms of life-years gained and quality-adjusted life years (QALYs). Health and economic outcomes were estimated from a public perspective and discounted at 5% per year over a 20-year horizon. Costs are reported in US dollars (US$) of 2019. A probabilistic sensitivity analysis was performed using life-years gained and QALYs.Results The CAIPaDi costs on average US$559 (95% CI: −$879 to −$239) less than the usual treatment (95% CI: −$879 to −$239) and produced a difference in mean life-years gained (0.48, 95% CI: 0.45 to 0.52) and mean QALYs (1.43, 95% CI: 1.40 to 1.46). The cost-effectiveness ratio resulted in a saving per life-year gained of −US$1155 (95% CI: −$1962 to −$460). Mean differences in QALYs resulted in a saving per QALY of −US$735 (95% CI: −$1193 to −$305). Probabilistic sensitivity analysis proved the results are robust on both life-years gained and QALYs.Conclusions CAIPaDi has a better cost-effectiveness ratio than the usual therapy in Mexican public health institutions.